The Impact of the BookTok Phenomenon on the Transformation of Generation Z's Reading Habits in the Digital Age in Indonesia - Judijanto, Loso; Hakim, Lukmanul; Utami, Wiwik Surya; Adiazmil, Aan (The Eastasouth Journal of Social Science and Humanities, 2025)
The rapid rise of BookTok, a book-related community on TikTok, has significantly impacted the reading habits of Generation Z in the digital age. This study examines the influence of the BookTok phenomenon on the reading behavior of Generation Z in Indonesia using a quantitative approach. A total of 120 participants completed a survey designed to assess their engagement with BookTok, reading frequency, genre preferences, and the adoption of digital reading platforms. Data were analyzed using SPSS version 25, employing descriptive statistics, reliability analysis, correlation, and regression analysis. The results show that higher engagement with BookTok is positively correlated with increased reading frequency, diversification of reading genres, and a preference for digital reading formats. The findings suggest that BookTok plays a significant role in shaping the reading habits of Generation Z by encouraging them to read more, explore various genres, and adopt digital reading technologies. These insights have implications for the publishing industry, educational institutions, and libraries in their efforts to engage younger generations with literature in the digital era.